Policy analysis for sustainable land management and food security in Ethiopia: a bioeconomic model with market imperfections - Holden, Stein; Shiferaw, Bekele A.; Pender, John L. (International Food Policy Research Institute, 2005)
Policy Analysis for Sustainable Land Management and Food Security in Ethiopia presents a bioeconomic model of this less- favored area in the Ethiopian highlands. The main reason for selecting this case study area is the unique availability of both biophysical and socioeconomic data covering a period of 15 to 20 years.The data provides a valuable opportunity to analyze the relationships between population pressure, poverty, and land degradation and to test policies for reducing vulnerability and improving sustainable management of the resource base.... Our analysis of the Andit Tid watershed community should be useful to policymakers and others seeking to reduce poverty and improve land management in Ethiopia and other countries where such problems are severe. Beyond this, the bioeconomic modeling approach used in this study can be usefully adapted and applied in many other settings.